2001
DOI: 10.1034/j.1600-0706.2001.920115.x
|View full text |Cite
|
Sign up to set email alerts
|

Separating the chance effect from other diversity effects in the functioning of plant communities

Abstract: Separating the chance effect from other diversity effects in the functioning of plant communitiesLeps, J; Brown, VK; Len, TAD; Gormsen, Dagmar; Hedlund, Katarina; Kailova, J; Korthals, GW; Mortimer, SR; Rodriguez-Barrueco, C; Roy, J; Regina, IS; van Dijk, C; van der Putten, WH Published in: Oikos DOI: 10.1034/j. 1600-0706.2001.920115.x 2001 Link to publication Citation for published version (APA): Leps, J., Brown, VK., Len, TAD., Gormsen, D., Hedlund, K., Kailova, J., ... van der Putten, WH. (2001). Separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
2
20

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 67 publications
(75 reference statements)
12
95
2
20
Order By: Relevance
“…Therefore, although we have focused on patterns of diversity in this study, the multiscale effects of non-native species we have described here may have broader implications for ecosystem functioning, affecting productivity, decomposition, and nutrient cycling (Van der Putten et al 2000;Lepš et al 2001).…”
Section: Native Alpha Vs Beta Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although we have focused on patterns of diversity in this study, the multiscale effects of non-native species we have described here may have broader implications for ecosystem functioning, affecting productivity, decomposition, and nutrient cycling (Van der Putten et al 2000;Lepš et al 2001).…”
Section: Native Alpha Vs Beta Diversitymentioning
confidence: 99%
“…Not all local communities are randomly assembled, however (Götzenberger et al 2012;Rajaniemi et al 2012). Some species may modify local habitat conditions upon arrival, and consequently influence the kind of species that can subsequently establish, facilitating some species with certain ecological traits, while inhibiting others with other traits (Weiher and Keddy 1995;Grime 1998;Lepš et al 2001;Fukami et al 2005). If so, local communities that vary stochastically in the timing of the arrival of key species can diverge in species composition, resulting in higher beta diversity than expected solely from environmental filtering and otherwise random assembly (Chase 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of a clear relationship between species richness and biomass production in a experimental grasslands (Leps et al, 2001) was also demonstrated by the lack of consistent differences between plots sown with low or high numbers of grassland species. The variance in the species composition between the different replicates of the Low diversity plots, as a consequence of their lower diversity, resulted in highly variable productivity.…”
Section: Productivity-diversity Relationshipmentioning
confidence: 96%
“…At local and regional scales, land use changes are among the most immediate drivers of species diversity. Intensification of land use, especially the conversion of natural ecosystems into agro-ecosystems is supposed to both change the composition and reduce the diversity of biological communities Leps et al, 2001). Therefore, one of the possibilities to counteract the current loss of biodiversity may be to reduce the intensity of land use (in the case of grassland), as well as to abandon cultivated land (in case of arable land).…”
Section: Land Use Changementioning
confidence: 99%
“…However, the cover crop, which introduced ten plant species to the system, had the same richness than the control. Thus, it seems that increasing plant species richness changed the structure of the native weed community by suppressing several species (Leps et al, 2001). Drought is believed to be partially responsible for the notable decline in plant species richness and density in 2007, year in which rainfall represented 29% of the previous year.…”
Section: Discussionmentioning
confidence: 99%